2016
DOI: 10.15452/cejnm.2016.07.0017
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing the effectiveness of clinical learning environment in nursing education

Abstract: Aim: The purpose of the cross-sectional descriptive study was to investigate how nursing students evaluate particular factors of clinical learning environment during their professional placement in hospitals. We explored which factors of clinical environment contribute significantly to students' evaluation of it. Design: A descriptive cross-sectional study. Methods: The sample included 503 nursing students in their second or third year of study at six Slovak universities. A valid and reliable questionnaire, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 14 publications
4
17
0
1
Order By: Relevance
“…We find that frequency of contact with private supervisor was associated with high evaluation of clinical experience by both nursing and midwifery students. These findings are consistent with the results from Cyprus [10], Slovakia [19], northern Italy [20] and Sweden [21] where nursing students evaluated their clinical experience better with private supervision. As team supervision was higher and likely to be poor among students, it is reasonable that contact with private supervisors with a high tendency for tailored training to receive high rating.…”
Section: Discussionsupporting
confidence: 91%
“…We find that frequency of contact with private supervisor was associated with high evaluation of clinical experience by both nursing and midwifery students. These findings are consistent with the results from Cyprus [10], Slovakia [19], northern Italy [20] and Sweden [21] where nursing students evaluated their clinical experience better with private supervision. As team supervision was higher and likely to be poor among students, it is reasonable that contact with private supervisors with a high tendency for tailored training to receive high rating.…”
Section: Discussionsupporting
confidence: 91%
“…We nd that frequency of contact with private supervisor was associated with high evaluation of clinical experience by both nursing and midwifery students. These ndings are consistent with the results from Cyprus [10], Slovakia [19], northern Italy [20] and Sweden [21] where nursing students evaluated their clinical experience better with private supervision. As team supervision was higher and likely to be poor among students, it is reasonable that contact with private supervisors with a high tendency for tailored training to receive high rating.…”
Section: Discussionsupporting
confidence: 91%
“…In another study conducted in Cyprus, the role of nursing teacher also achieved the highest score (Dimitriadou et al, 2015). Pedagogical atmosphere on the ward was the second least important sub-dimension in the current study (3.77 ± 0.70), a finding in line with that of another study conducted in Slovakia in which students ranked it as the least important sub-dimension (Gurková et al, 2016). A study conducted on internship nurses in Egypt found pedagogical atmosphere most important in terms of CLES+T score (81.7%) (Makhlof et al, 2017).…”
Section: Discussionsupporting
confidence: 90%